SELECTIVE TRANSPORT AND EXTRACTION OF ALKALI METAL CATIONS (Na & K ) THROUGH CHLOROFORM LIQUID MEMBRANE BY DIETHYLENE GLYCOL MONOBUTYL ETHER AND DIETHYLENE GLYCOL DIBUTYL ETHER (Journal of Sciences, Islamic Republic of Iran)
A liquid membrane containing diethylene glycol monobutyl ether (2) shows specificity for K ion in transport while diethylene glycol dibutyl ether (1) was selective for Na over K . As an extractant, ligand 2 exhibited pronounced extraction selectivity for K over Na in comparison with ligand 1